MODELING OF THE CONCEPT OF LIFE USING A FRAME STRUCTURE (on the Materials of Amelie Notomb’s Novel "The Character of Rain") - Myronova, Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article considers the correlation of cognitive linguistics key notions, such as "frame" and "concept". The frame is presented as a structure of data or knowledge about any notion, concept – as a complicated and multidimensional mental complex, which in addition to the notional basis also has socio-psycho-cultural component. Interpretation of the concept implies that it has a wide semantic field. A frame with its clearer structure can be used to model or structure the concept, i.e. the concept can be represented as a frame structure. A description of the experience of modeling the LIFE concept using a frame structure by identifying subframes and analyzing their deployment in Amelie Notomb’s novel "The Character of Rain" is presented. According to the method of semantic-cognitive frames analysis of a fictional work, it is determined that the frame structure of the LIFE concept unites 9 slots (mental nodes of the frame structure): EXISTENCE, MOVEMENT, DESTRUCTION OF DREAM, DEGRADATION, EMPTINESS, DEVELOPMENT, INDEPENDENCE, DISAPPOINTMENT, SUICIDE. Deployment of the LA VIE frame, which goes in the direction of such subframes as L’EXISTENCE, LE MOUVEMENT, LA DESTRUCTION DU RÊVE, is reflected in the subframes DÉGRADATION, LE VIDE, LE DÉVELOPPEMENT, L’INDÉPENDANCE, LA DÉCEPTION, LE SUICIDE. This process is due to the fact that the life of a person who feels nothing and rejoices in nothing is an existence: miserable, ordinary, boring, meaningless. EXISTENCE, invaded by a disease, sooner or later leads to the DEGRADATION in all spheres of activity. The result is EMPTINESS, everything becomes the same: it does not matter if something bad or, conversely, something joyful occurs. MOVEMENT is an important component of a full life. It leads to the DEVELOPMENT of both: physical and individual development in society. Movement means autonomy, and as a consequence, INDEPENDENCE. DISAPPOINTMENT appears when you realize, that people you are closest to do not understand you at all: they have no idea what you enjoy, what makes you laugh, what is a pleasure for you and what you are capable of. When you realize that society does not need you, when you are deprived of what you are used to and of what is most precious to you in the world, it leads to SUICIDE. These subframes are reflected in the DREAM DESTRUCTION subframe. Involvement of semantic-cognitive methods complex in the study of frames reveals their cognitive-communicative dynamics. Thus, underlying semantic processes that take place in the literary text, reflect the tendency to unfold the frames. We can assume that the frame structure of the LIFE concept is the result of generalization of the vocabulary meaning of the word and the individual author’s sphere of concepts. ______________ REFERENCES • Baranov, A. N. Vvedenie v prikladnuyu lingvistiku [Introduction to Applied Linguistics] (Moskva, LKI, 2007), 360 (In Russ.). • Gurina, R. V., Sokolova, E. E. Freymovoe predstavlenie znaniy: monografiya [Frame representation of knowledge: monograph]. (Moskva, Narodnoe obrazovanie, 2005), 175 (In Russ.). • Zhabotinskaya, S. A. «Kognitivnaya lingvistika: printsipy kontseptual’nogo modelirovaniya [Cognitive linguistics: principles of conceptual modeling].» Lіngvіstichnі studії [Linguistic Studios] 2 (1997): 3-11 (In Russ.). • Zharkynbekova, Sh. K. «Modelirovanie kontsepta kak metod vyyavleniya etnokul’turnoy spetsifiki [Concept modeling as a method for identifying ethnocultural specifics].» Materialy IX Kongressa MAPRYaL [Materials of the IX MAPRYAL Congress]. (1992): 25 (In ). • Kaghanovsjka, O. M. «Tekstovi koncepty khudozhnjoji prozy (na materiali francuzjkoji romanistyky seredyny KhKh storichchja) [Textual concepts of fiction (based on French novels of the mid-twentieth century)].» (Kyjiv, KNLU, 2002), 292 (In ). • Myronova, N. V. «Code linguoculturel: base théorique de la recherche.» Problemy semantyky, praghmatyky ta koghnityvnoji linghvistyky [Problems of semantics, pragmatics and cognitive linguistics] 35 (2019): 13-25. • Myronova N. V. «Expansion des codes culturels au langage naturel.» Ljvivsjkyj filologhichnyj chasopys [Lviv Philological Journal] 6 (2019): 153- • Nikonova, Zh. V. Teoriya freymov v lingvisticheskikh issledovaniyakh [Frame theory in linguistic research] (Sankt-Peterburg, Filologicheskiy fakul’tet SpbGU, 2006), 144. • Tarasova, I. A. Poeticheskiy idiostil’ v kognitivnom aspekte [Poetic idiostyle in the cognitive aspect] (Moskva, Flinta, 2017), 196. • Fillmore, J. «Frame Semantics and the Nature of Language.» Origins and Evolution of Language and Speech (1976): 20-32. • Minsky, A «Framework for Representing Knowledge.» The Psychology of Computer Vision (1975): 211-277. • Nothomb, Métaphysique des tubes (Paris, Albin Michel S.A., 2000), 162.